2016
DOI: 10.3389/fneur.2016.00045
|View full text |Cite
|
Sign up to set email alerts
|

Blepharospasm: Update on Epidemiology, Clinical Aspects, and Pathophysiology

Abstract: Blepharospasm (BSP) is a rather distressing form of focal dystonia. Although many aspects of its pathophysiological mechanisms are already known, we lack fundamental evidence on etiology, prevention, and treatment. To advance in our knowledge, we need to review what is already known in various aspects of the disorder and use these bases to find future lines of interest. Some of the signs observed in BSP are cause, while others are consequence of the disorder. Non-motor symptoms and signs may be a cue for under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
61
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 68 publications
1
61
1
2
Order By: Relevance
“…Different brain regions have been shown to function abnormally in the blepharospasm, including the basal ganglia, the cortex, and the cerebellum. However, it is unclear whether the functional changes in these sites are the cause or outcome of the disease [2]. The precise neural circuitry involved in the pathogenesis of essential blepharospasm is not clear either.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different brain regions have been shown to function abnormally in the blepharospasm, including the basal ganglia, the cortex, and the cerebellum. However, it is unclear whether the functional changes in these sites are the cause or outcome of the disease [2]. The precise neural circuitry involved in the pathogenesis of essential blepharospasm is not clear either.…”
Section: Discussionmentioning
confidence: 99%
“…Severe blepharospasm may cause traffic accidents [1]. Since the etiology and mechanism of essential blepharospasm is unknown, current treatment is mostly directed to relief the symptoms [2]. Many therapies such as biofeedback, hypnosis, acupuncture, psychotherapy have been tried but with little success.…”
Section: Introductionmentioning
confidence: 99%
“…This disease occurs mostly in adults and manifested with an increased frequency of blinking in the early stage and consistent closed-eyes or even functional blindness in the late stages. Furthermore, BSP will lead to poor quality of life, decline in employment, anxiety, and depression ( Muller et al, 2002 ; Biuk et al, 2013 ; Valls-Sole and Defazio, 2016 ; Bedarf et al, 2017 ). However, the pathophysiology of BSP remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Blepharospasm is a form of focal dystonia characterized by involuntary orbicularis oculi muscle spasms ( 4 , 5 ). Studies of patients with blepharospasm have demonstrated hyperactivity of various brain regions, including the lenticular nucleus and thalamus ( 4 ). Recent studies also demonstrated cerebellar involvement in blepharospasm patients ( 4 , 6 ).…”
Section: Introductionmentioning
confidence: 99%